(untitled) (Research, Society and Development, 2021)
Oxidation affects in vitro growth, due to the release of phenolic compounds, resulting in tissue darkening and, consequently, in the death of explants and plants. Therefore, this work aimed to study the effect of ascorbic acid and polyvinylpyrrolidone (PVP) in the in vitro cultivation of yam, aiming at reducing or eliminating the oxidation of explants and optimizing the growth of genotypes D. alata var. purpurea (Roxb.) A. Pouchet and D. rotundata Poir. In this experiment, nodal segments of approximately 1 cm in size, extracted from plants previously cultivated in vitro, were introduced into test tubes containing 10 mL of 2GGC culture medium, added with 30 g L-1 of sucrose, solidified with 2.2 g L-1 of Phytagel® and pH adjusted to 5.8 before autoclaving. Two antioxidants were added to the basic medium, making up two distinct experiments. In the first experiment, ascorbic acid was used at concentrations of 0 mg L-1; 25mg L-1; 50 mg L-1; 75 mg L-1 and 100 mg L-1; and in the second, PVP, at doses of 0 mg L-1; 50 mg L-1; 100 mg L-1; 150 mg L-1 and 200 mg L-1. Each experiment was installed in a completely randomized design, in a 5 x 2 factorial scheme (antioxidant concentrations x genotypes), containing 12 replicates per treatment. After 90 days of maintenance in the growth room, plant development was evaluated and it was observed that the antioxidants ascorbic acid and polyvinylpyrrolidone did not improve the growth variables.